1993
DOI: 10.1111/j.1440-1827.1993.tb01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed medullary and follicular carcinoma of the thyroid: Report of two cases with an immunohistochemical study

Abstract: Two cases of mixed medullary and follicular carcinoma of the thyroid (MFC) and two cases of thyroid carcinoma resembling MFC are reported with a description of their histological and immunohistochemical features. Two cases of MFC with lymph node metastasis were histologically distinguishable from each other because one had a follicular structure filled with a thyroglobulin (TG)‐positive colloid‐like substance and the other did not have it. Although one of the thyroid carcinomas resembling MFC was similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…9,11,12 Interestingly, a number of cases of thyroid cancer with a mixed medullary and follicular pattern have been reported. [3][4][5][6][7][8][9][10][11][12][13][14][15] Many investigators believe that mixed medullary and follicular carcinoma of the thyroid is derived from neoplastically transformed uncommitted stem cells with the capacity to differentiate into tumor components with morphological and histochemical 16 suggested that the follicular and medullary components in mixed medullary and follicular carcinoma are not derived from a single progenitor cell, because they observed different patterns of RET proto-oncogene mutation, LOH, and X-chromosomal inactivation (clonality) is seven tumors. According to Matias-Guiu, 17 confirmation of the so-called "hostage hypothesis" would require the unknown tropic factors necessary for the stimulation of follicular cells, as well as the detection of these substances in the medullary thyroid cells of mixed medullary and follicular carcinomas and their absence in classical medullary thyroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,12 Interestingly, a number of cases of thyroid cancer with a mixed medullary and follicular pattern have been reported. [3][4][5][6][7][8][9][10][11][12][13][14][15] Many investigators believe that mixed medullary and follicular carcinoma of the thyroid is derived from neoplastically transformed uncommitted stem cells with the capacity to differentiate into tumor components with morphological and histochemical 16 suggested that the follicular and medullary components in mixed medullary and follicular carcinoma are not derived from a single progenitor cell, because they observed different patterns of RET proto-oncogene mutation, LOH, and X-chromosomal inactivation (clonality) is seven tumors. According to Matias-Guiu, 17 confirmation of the so-called "hostage hypothesis" would require the unknown tropic factors necessary for the stimulation of follicular cells, as well as the detection of these substances in the medullary thyroid cells of mixed medullary and follicular carcinomas and their absence in classical medullary thyroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…MMFC are very rare tumors, accounting for less than 0.2% of all thyroid tumors [34,56]. As for conventional medullary carcinoma, MMFC may arise as sporadic tumors, in the vast majority of reported cases, or associated with MEN2 syndrome [38,43,47,55], both type 2A and type 2B.…”
Section: Meec In the Pancreas Gastrointestinal And Biliary Tractmentioning
confidence: 99%
“…Medullary carcinomas comprise 5–10% of all thyroid carcinomas in humans, and only 3–5% of these neoplasms (~0.15% of all thyroid tumors) display mixed features, having a follicular or papillary carcinoma component in the primary medullary carcinoma or in the metastases, or in both. 1,3,4,8,10 Mixed medullary-follicular thyroid carcinoma have not been reported in dogs, to our knowledge, and the WHO International Classification of Tumors of Domestic Animals does not include this entity. 2…”
mentioning
confidence: 95%